Men's Activism to End Violence Against Women Voices from Spain, Sweden and the UK - Westmarland, Nicole (Policy Press, 2021)
"EPUB and EPDF available Open Access under CC-BY-NC-ND licence. Using case studies from Europe and the UK, this book highlights those men who are taking action to eradicate violence against women. Examining the factors that support men to take a public stance, the authors also demonstrate what we can learn from their experiences to help build the movement to end violence against women. This important study will inform grassroots movements working to involve and engage men and boys in building gender equality."